Beat the heat - Periard, J. D.; Stevenson, B. T.; Goosey-Tolfrey, J. L.; Nikopoulos, T.; Migliorini, S. (2020)
Contents How is core temperature regulated? How does environmental heat stress affect triathlon performance? How does environmental heat stress affect athlete health? How to best prepare for competing in the heat? What sort of performance benefit can I expect from heat acclimation? What type of approach should I use in order to heat acclimate? How and when do I implement heat acclimation in my regimented training program? What pre-cooling strategies can I use before a race? What about during the race? How does hydration status influence performance? How much should I drink? What should I drink? How is environmental heat stress determined? What are the new ITU rules to help mitigate heat stress? References